Multikulturalisme Di Indonesia: Pengalaman Masa Kemerdekaan - Nurhidayat Nurhidayat; Jamali Syahrodi; Siti Fatimah (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2023)
Life in this universe turns out to have diversity. In Indonesia, there are various backgrounds of different religions, ethnicities, languages, races, skin colors and different artistic and cultural traditions, as well as the heritage of the ancestral nation which is truly protected. This study uses a qualitative research method with a descriptive analysis approach that describes multiculturalism in Indonesia: The Experience of the Independence Period seen from the past history after Indonesia's independence. Multiculturalism is an ideology that recognizes and respects the equality of existing cultural differences. Islamic religious teachings which always precipitate, kinship togetherness and harmony which is contained in a term al-maqashdudsysyar'i (religious goals) as a form of unified whole and being independent that stands in the midst of differences. The forms of multiculturalism in Indonesia include in the political, cultural, economic and social fields. One example in the political field is the four pillars or four shared contexts, namely ideology, law, diversity, and motto, in the cultural field, for example, hospitality among citizens, to guests, speaking politely, being polite and welcoming to nyimah in Lampung, in in the economic field, he recognized shari'ah insurance and shari'ah banking, and in the social field, for example, Chinese citizens and Arab citizens were accepted as Indonesian citizens.